Presence of asbestiforms minerals in vermiculite: Province of Córdoba, Argentina - Lescano, Leticia (2011)
Presence of asbestos in a vermiculite mine was identified in Argentina. Vermiculite has the property of expanding itself nearly 20 times its original size when heated. This process, called exfoliation, releases asbestos fibers from the vermiculite ore into the air, where they can be inhaled by people who work in the mines or live in bordering zones. Inhalation of asbestos fibers suspended in air can result in lung diseases such as asbestosis, mesothelioma and lung cancer.